Hydroxyapatite synthesis and characterization from marine sources: A comparative study - Krishna Meghal Balabadra; Suganya Panneer Selvam; Ramya Ramadoss; Sandhya Sundar (Journal of Oral Biology and Craniofacial Research)
Background: Hydroxyapatite (HAP) is a biocompatible material widely used in biomedical applications. Recent studies have explored various marine sources for HAP synthesis, demonstrating its potential for diverse applications. Objective: This study aims to compare the characteristics of hydroxyapatite synthesized from sea shells and fish bones, specifically from the shells of Scylla olivacea (orange mud crab) and bones of Eleutheronema tetradactylum (fourfinger threadfin). Materials & methods: HAP was synthesized from Scylla olivacea shells and Eleutheronema tetradactylum bones. The synthesized HAP underwent comprehensive characterization, including scanning electron microscopy (SEM) for structural analysis, hemocompatibility testing, antibacterial assays, and energy-dispersive X-ray spectroscopy (EDS) analysis. Results: SEM revealed a complex structure of HAP with a clustered arrangement and biofilm-like features. HAP derived from crab shells exhibited superior structural properties compared to that from fish bones. Both sources demonstrated good hemocompatibility, essential for biomedical applications. The antibacterial assays indicated effective antibacterial properties for both HAP sources, with crab shell-derived HAP showing slightly better performance. EDS analysis confirmed the presence of key elements necessary for HAP, with a consistent composition in both sources. Conclusion: Our study concludes that hydroxyapatite derived from Scylla olivacea shells exhibits superior properties compared to that from Eleutheronema tetradactylum bones. This research establishes a precedent for future investigations into other marine species, thereby broadening the scope and potential of hydroxyapatite synthesis from natural sources.